Healthy Lifestyle Behaviors and Their Association with Self-Regulation in Chilean Children - Fernandez-Vergara, O; Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Background: Self-regulation comprises a series of important competencies, such as the ability to control inner states or responses toward thoughts, attention, emotions, or even performance. The relationship between self-regulation and different healthy lifestyle behaviors among children has not been examined in depth to date. The aim of this study was to explore the association between physical activity, screen time levels, and/or Mediterranean Diet adherence and self-regulation in Chilean children. Methods: A total of 1561 children aged 8–12 years from eight public schools with low socioeconomic status were included. Physical activity, screen time, Mediterranean Diet, and self-regulation were assessed with validated questionnaires. Results: Children who were classified as active or those who reported less than 2 h per day of screen time had higher self-regulation than those who were classified as inactive or counterparts with 2 h per day or more of screen time, respectively. Using joint categories, active children both with low and high screen time showed higher self-regulation compared to inactive/high screen time peers. Additionally, active groups with adherence or non-adherence to the Mediterranean Diet had higher self-regulation compared to inactive and non-adherence peers. Conclusion: Having a greater number of healthy habits, mainly regular physical activity, was associated with higher self-regulation, which might be one potential strategy to promote child social-emotional development. © 2020 by the authors.